Impact of systemic hypoxia and blood flow restriction on mechanical, cardiorespiratory, and neuromuscular responses to a multiple-set repeated sprint exercise - Solsona, Robert; Dériaz, Roméo; Albert, Simon; Chamoux, Maxime; Lloria-Varella, Jaume; Borrani, Fabio; Sanchez, Anthony M. J. (Frontiers in Physiology, 2024)
Repeated sprint cycling exercises (RSE) performed under systemic normobaric hypoxia (HYP) or with blood flow restriction (BFR) are of growing interest. To the best of our knowledge, there is no stringent consensus on the cardiorespiratory and neuromuscular responses between systemic HYP and BFR during RSE. Thus, this study assessed cardiorespiratory and neuromuscular responses to multiple sets of RSE under HYP or with BFR. According to a crossover design, fifteen men completed RSE (three sets of five 10-s sprints with 20 s of recovery) in normoxia (NOR), HYP, and with bilaterally-cuffed BFR at 45% of resting arterial occlusive pressure during sets in NOR. Power output, cardiorespiratory and neuromuscular responses were assessed. Average peak and mean powers were lower in BFR (dz=0.87 and dz=1.23, respectively) and HYP (dz=0.65 and dz=1.21, respectively) compared to NOR (p<0.001). The percentage decrement of power output was greater in BFR (dz=0.94) and HYP (dz=0.64) compared to NOR (p<0.001), as well as in BFR compared to NOR (p=0.037, dz=0.30). The percentage decrease of maximal voluntary contraction of the knee extensors after the session was greater in BFR compared to NOR and HYP (p=0.011, dz=0.78 and p=0.027, dz=0.75, respectively). Accumulated ventilation during exercise was higher in HYP and lower in BFR (p=0.002, dz=0.51, and p<0.001, dz=0.71, respectively). Peak oxygen consumption was reduced in HYP (p<0.001, dz=1.47). Heart rate was lower in BFR during exercise and recovery (p<0.001, dz=0.82 and p=0.012, dz=0.43, respectively). Finally, aerobic contribution was reduced in HYP compared to NOR (p=0.002, dz=0.46) and BFR (p=0.005, dz=0.33). Thus, this study indicates that power output during RSE is impaired in HYP and BFR and that BFR amplifies neuromuscular fatigue. In contrast, HYP did not impair neuromuscular function but enhanced the ventilatory response along with reduced oxygen consumption.